SISTEM KEAMANAN AKTIVITAS KOMPUTER ANAK BERBASIS OPENSOURCE - Syafri Arlis (Universitas Negeri Padang, 2016)
Technological developments at the present time is very rapid, starting from local access to be able to access information of the world. But behind it all the time management in the use of computers should be is arranged, especially in children. Parents must be responsible and can adjust their schedules, especially in scheduling use of a home computer. So that use can be controlled schedule and could make children more independent and disciplined. Designing an application form Parental Control can minimize the child in excessive computer use.